Diuretic activity of aqueous extract of roots of Cissampelos pareira in albino rats - Sayana, Suresh Babu; Khanwelkar, Chitra C.; Nimmagadda, Venkat Rao; Chavan, Vasant R.; Sambu, Naveen Kumar (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Diuretic compounds that stimulate the excretion of water with small traceable ions are potentially useful in most of disorders including those exhibiting edema such as congestive heart failure, nephritis, toxemia of pregnancy, premenstrual tension, and hypertension. The aim was to evaluate the diuretic activity of aqueous extract of roots of Cissampelos pareira (AQERCP) by Lipschitz method in albino rats. Methods: Five groups of Albino rats were used to evaluate the diuretic activity of AQERCP by using metabolic cages. The Group I serves as normal control received vehicle (carboxymethyl cellulose 2% in normal saline), the Group II furosemide (10 mg/Kg, p.o) in vehicle; other Groups III, IV, and V were treated with low (100 mg/kg), medium (200 mg/kg), and high (400 mg/kg) doses of AQERCP in vehicle. Immediately, after the extract treatment all the rats were hydrated with saline (15 ml/kg, p.o) and placed in the metabolic cages (3/cage), specially designed to separate urine and faeces, kept at 21°C±0.5°C.The total volume of urine collected was measured at the end of 5th hr. During this period, no food and water was made available to animals. Various parameters such as total urine volume and concentration of sodium, potassium, chloride ions in the urine were measured and estimated respectively. Results: In this model, when compared to vehicle treated control group the AQERCP at different dose levels (100, 200 and 400 mg/kg) has significantly increased the urine volume and also enhanced the elimination of sodium, potassium and chloride ions in urine. Conclusion: The results showed that single dose administration of AQERCP as 100, 200 and 400 mg/Kg and standard frusemide (10 mg/kg b.wt) has significantly (p<0.05*, p<0.01**, p<0.001***) increased the urine output along with an increase in concentration of sodium, potassium, and chloride. AQERCP 400 mg/Kg produced a greater diuretic activity, which is comparable to the effect of standard furosemide (10 mg/kg).The present study has supported and justified the basis for folklore use of roots of C. pareira as a diuretic agent.